Analysis and Optimization of Dynamic Measurement Precision of Fiber Optic Gyroscope. (28th November 2013) - Li, Hui; Cui, Liyang; Lin, Zhili; Zhang, Chunxi
Abstract : In order to improve the dynamic performance of high precision interferometer fiber optic gyroscope (IFOG), the influencing factors of the fast response characteristics are analyzed based on a proposed assistant design setup, and a high dynamic detection method is proposed to suppress the adverse effects of the key influencing factors. The assistant design platform is built by using the virtual instrument technology for IFOG, which can monitor the closed-loop state variables in real time for analyzing the influence of both the optical components and detection circuit on the dynamic performance of IFOG. The analysis results indicate that nonlinearity of optical Sagnac effect, optical parameter uncertainty, dynamic characteristics of internal modules and time delay of signal detection circuit are the major causes of dynamic performance deterioration, which can induce potential system instability in practical control systems. By taking all these factors into consideration, we design a robust control algorithm to realize the high dynamic closed-loop detection of IFOG. Finally, experiments show that the improved 0.01 deg/h high precision IFOG with the proposed control algorithm can achieve fast tracking and good dynamic measurement precision.